2016
DOI: 10.1155/2016/6374584
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Gallium-67 Accumulation in the Left Atrial Wall Detected Using SPECT/CT Fusion Images

Abstract: Gallium-67 scintigraphy is useful for detecting active inflammation. We show a 66-year-old female patient with atrial fibrillation and diffuse thickening of the left atrial wall due to acute myocarditis, who presented diffuse abnormal accumulation of gallium-67 in the left atrium on single photon emission computed tomography/computed tomography (SPECT/CT) fusion images. In the second gallium-67 scan 2 months after the first scintigraphy, the abnormal accumulation in the heart was no longer visible. Gallium-67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…We did not perform visual and semiquantitative assessments of the radiopharmaceutical accumulation in the left atrial walls because radioactive pool of blood in the left atrial cavity could be easily confused with the focal pathological accumulations, whereas histological sampling in this zone for comparative evaluation was not feasible. Nevertheless, Kotani et al [35] reported feasibility of visualization of the atrial myocardium based on SPECT/CT with Gallium-67. Authors reported that the use of this method was necessary to clarify localizations of radiopharmaceutical accumulation in cases when the accumulation was present on the planar images.…”
Section: Discussionmentioning
confidence: 99%
“…We did not perform visual and semiquantitative assessments of the radiopharmaceutical accumulation in the left atrial walls because radioactive pool of blood in the left atrial cavity could be easily confused with the focal pathological accumulations, whereas histological sampling in this zone for comparative evaluation was not feasible. Nevertheless, Kotani et al [35] reported feasibility of visualization of the atrial myocardium based on SPECT/CT with Gallium-67. Authors reported that the use of this method was necessary to clarify localizations of radiopharmaceutical accumulation in cases when the accumulation was present on the planar images.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of nuclear imaging to the diagnosis of cardiomyopathies is limited except in the diagnosis and prognosis of sarcoidosis and TTR-associated amyloidosis [43]. Previously, thallium-201 and gallium-67 radionuclide scintigraphy provided diagnostic and prognostic assessment of sarcoidosis [46]. Accumulated gallium-67 is an indication of active inflammation associated with sarcoidosis or acute myocarditis.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…After screening all the potential studies against the inclusion criteria, fourteen (14) studies investigating DCM diagnosis were included in the present meta-analysis [30,[46][47][48][49][50][51][52][53][54][55][56][57][58]. The studies were published between 1994 and 2017.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations